2014
DOI: 10.1097/wnf.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of D-Cycloserine to Treat Stereotypies in Older Adolescents and Young Adults With Autism Spectrum Disorder

Abstract: Objectives Autism spectrum disorders (ASDs) have core impairments in social communication as well as the presence of repetitive, stereotypic behaviors and restricted interests. Older adolescents and young adults are particularly impacted by these deficits. Preclinical data implicate glutamatergic dysfunction in the pathophysiology of ASDs. D-Cycloserine (DCS), a partial glycineB agonist at the N-methyl-D-aspartic acid receptor site, has been shown to improve sociability in mouse models and a small human study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
(42 reference statements)
1
38
0
Order By: Relevance
“…In a recent clinical trial carried out on 20 patients with autism, it has been shown that D‐cycloserine treatment alleviated the stereotyped behavior of these patients (Urbano et al., 2014). To go more into details, the administration of D‐cycloserine during 8 weeks with different dosages showed to be effective on ASD manifestations in these patients without showing any side effects (Urbano et al., 2014).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent clinical trial carried out on 20 patients with autism, it has been shown that D‐cycloserine treatment alleviated the stereotyped behavior of these patients (Urbano et al., 2014). To go more into details, the administration of D‐cycloserine during 8 weeks with different dosages showed to be effective on ASD manifestations in these patients without showing any side effects (Urbano et al., 2014).…”
Section: Reviewmentioning
confidence: 99%
“…To go more into details, the administration of D‐cycloserine during 8 weeks with different dosages showed to be effective on ASD manifestations in these patients without showing any side effects (Urbano et al., 2014). Additional studies will be required to determine the therapeutic effect of this drug in ASD.…”
Section: Reviewmentioning
confidence: 99%
“…In a 2-week, pilot, single-blind placebo lead-in study with children, adolescent and young adults with ASD (N=10; mean age 10.0±7.7; range 5–28 years), D-cycloserine resulted in significant improvement in the social withdrawal subscale of the Aberrant Behavioral Checklist (ABC-SW) [45]. In a double-blind randomized, 10-week pilot study (N=20; age range 14–25 years), the result on improvement in ABC-SW by D-cycloserine was not replicated [46]. However, D-cycloserine was found to reduce stereotypic symptoms (as measured by stereotypy subscale of the ABC) in young adults and adolescents [46].…”
Section: Current Evidence Of Efficacy For Glutamatergic Agents In mentioning
confidence: 99%
“…Buspirone [95,[201][202][203], fluoxetine [204][205][206][207][208], escitalopram [209,210], citalopram [211], sertraline [212][213][214], D cycloserine [186,[215][216][217][218], amantadine [219], and memantine [220][221][222] have already been used in clinical research into autism. Finally, naltrexone, a potent opiate antagonist tested in ASD for improving behavioral changes [223][224][225][226][227][228][229][230][231][232][233][234][235][236][237][238][239], could also possess immunomodulatory action [240].…”
Section: Discussionmentioning
confidence: 99%